2010
DOI: 10.1590/s0103-21002010000300014
|View full text |Cite
|
Sign up to set email alerts
|

Resistência à mupirocina entre isolados de Staphylococcus aureus de profissionais de enfermagem

Abstract: RESUMO ABSTRACT Objectives:To assess colonization by Staphylococcus aureus sensitive and resistant to methicillin found in the saliva of nurses and, to recognize the mupirocin profile of resistance. Methods: It was collected three saliva samples of 356 (94.2%) professional research participants, totaling 1068 samples processed. All ethical aspects were covered. Microbiological analysis included the phenotypic identification, according to the standards of the Clinical and Laboratory Standards Institute. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(21 reference statements)
1
7
0
1
Order By: Relevance
“…[2][3][4][5][6][7][8][9] Asymptomatic carriers of Staphylococcus aureus may act as disseminators of the microorganism to a population susceptible to colonization. 10 Approximately 20% of the population may be considered persistent carriers, 60% transitory carriers, and the remaining 20% do not present colonization by Staphylococcus aureus.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Asymptomatic carriers of Staphylococcus aureus may act as disseminators of the microorganism to a population susceptible to colonization. 10 Approximately 20% of the population may be considered persistent carriers, 60% transitory carriers, and the remaining 20% do not present colonization by Staphylococcus aureus.…”
mentioning
confidence: 99%
“…In the United States there is about 94,000 individuals infected with MRSA and about 18% result in death. Most invasive MRSA infections (86%) occurred in individuals with previous exposure to a hospital environment or the health care service [20].…”
Section: Discussionmentioning
confidence: 99%
“…In various studies on healthcare workers, scientific evidence has shown the presence of methicillin-resistant Staphylococcus aureus (MRSA), Staphylococcus ssp, Enterococcus faecalis, Acinetobacter baumannii, Streptococcus ssp and Serratia ssp, colonizing the nasal cavity, white coats and saliva of hospital workers. (2)(3)(4) Direct contact between health workers and infected patients can propagate the contamination of these superbugs, which increases the possibility of professionals acquiring resistance to available antimicrobials for treating diseases. (2) To prevent this risk, individual and collective protection measures need to be adopted.…”
Section: Introductionmentioning
confidence: 99%
“…(2)(3)(4) Direct contact between health workers and infected patients can propagate the contamination of these superbugs, which increases the possibility of professionals acquiring resistance to available antimicrobials for treating diseases. (2) To prevent this risk, individual and collective protection measures need to be adopted. Workers should use personal protective equipment (PPE) that is appropriate for the type of work being performed and under adequate working conditions.…”
Section: Introductionmentioning
confidence: 99%